Giant electrocaloric effect in 0.75PbZrO3 - 0.25Bi(Mg1/2Ti1/2)O3 ceramics. Issue 11 (1st August 2019) - Jamwal, Tanya; Kumar, Raju; Singh, Satyendra
Abstract: Antiferroelectric (AFE)/ferroelectric (FE) materials with large electrocaloric effect (ECE) in a broad operating temperature range are potential candidates for next generation solid-state refrigeration applications due to its environmentally-friendly and high efficiency. In this work, we have experimentally investigated the electrocaloric response in 0.75PbZrO3 -0.25Bi(Mg1/2 Ti1/2 )O3 in ceramics by prepared by a standard solid-state reaction method. Ferroelectric P-E hysteresis loops were measured over a broad range of temperature/electric field and the ECE was calculated by the indirect thermodynamic method. The maximum value of ECE ( Δ T) and the electrocaloric responsivity ( Δ T/ Δ E) were found to be 0.96K and 2.43 × 10 −7  K.mV −1, respectively, at an operating temperature of 366 K under the external electric field of 40kV/cm. The observed ECE response has the great potential for their uses in solid state cooling technology applications.